Humanisasi Teknologi Pendidikan Melalui Perspektif Pancasila: Tinjauan Filosofis Dan Normatif: Humanization of Educational Technology Through a Pancasila Perspective: Philosophical and Normative Review - Andyen Arvelia Devi Susanto; Alicya Askiyatu Zahro; Fildzah Khairina Mazaya; Salsa Sabila; Reni Arfiani; Ayu Raras Anggrayny (LITERA: Jurnal Ilmiah Mutidisiplin, 2025)
The development of educational technology in the digital age brings great opportunities for improving the quality of learning, but also poses the risk of dehumanization if humans are positioned solely as objects of the technological system. Pancasila, as the philosophical foundation of the Indonesian nation, provides a normative and philosophical framework to ensure that the use of educational technology remains oriented towards human dignity through philosophical and normative review. This study emphasizes that the principles of Pancasila, such as just and civilized humanity, social justice, and deliberation, are important foundations in developing a humanistic educational technology paradigm. Thus, the humanization of educational technology is not only technically adaptive, but also internalizes the values of Pancasila to create an inclusive, ethical, and equitable learning process.